Microscopic messengers: Extracellular vesicles shaping gastrointestinal health and disease - Zhantao Yu; Kevin A. Swift; Madeline A. Hedges; Arianne L. Theiss; Sarah F. Andres (Physiological Reports)
Abstract The field of extracellular vesicles (EVs) is advancing rapidly, and this review aims to synthesize the latest research connected to EVs and the gastrointestinal tract. We will address new and emerging roles for EVs derived from internal sources such as the pancreas and immune system and how these miniature messengers alter organismal health or the inflammatory response within the GI tract. We will examine what is known about external EVs from dietary and bacterial sources and the immense anti‐inflammatory, immune‐modulatory, and proliferative potential within these nano‐sized information carriers. EV interactions with the intestinal and colonic epithelium and associated immune cells at homeostatic and disease states, such as necrotizing enterocolitis (NEC) and inflammatory bowel disease (IBD) will also be covered. We will discuss how EVs are being leveraged as therapeutics or for drug delivery and conclude with a series of unanswered questions in the field.